Clinical efficacy of a virtual reality tool for the treatment of obesity: study protocol of a randomised controlled trial - Dimitra Anastasiadou; Jose Antonio Ramos-Quiroga; Mel Slater; Bernhard Spanlang; Desiderio Cano Porras; Marta Comas; Andreea Ciudin; Gemma Parramon Puig; Julia Vázquez-De Sebastián; Pilar Lusilla-Palacios (BMJ Open)
Introduction Previous research has shown that it is feasible to integrate motivational interviewing techniques with behavioural and psychological interventions for the treatment of obesity. Moreover, these combined interventions have the potential to improve health-related outcomes of people living with obesity (PLWO) and to afford maintenance of behavioural changes over time. In addition, the use of virtual reality (VR) embodiment techniques in the treatment of eating disorders and obesity has promising preliminary effectiveness. The objective of this study is to assess the clinical efficacy of a VR intervention that uses embodiment and body-swapping techniques and has been specifically developed to cover the needs of PLWO.Methods and analysis A randomised control trial will be carried out with an estimated sample of 96 participants with body mass index (BMI)>30. The whole duration of the trial will be 12 months. Participants will be recruited from the external consultations of the Vall d'Hebron University Hospital and be randomly assigned to three groups. The experimental group 1 will engage in a virtual self-conversation using the ConVRself platform, the experimental group 2 will participate in a ‘pre-established discourse’ provided by the virtual counsellor, who will give psychoeducation advice, and the control group will continue with treatment as usual. Readiness to change, BMI, eating habits and physical activity, psychological well-being, body image satisfaction, quality of life in relation to body image, and weight bias internalisation will be assessed at baseline, post intervention, 1-week and 4-week follow-up. Finally, variables related to adherence and satisfaction with the VR tool will be evaluated for the experimental groups.Ethics and dissemination This study was approved by the Research Projects Committee of the Vall d’Hebron University Hospital. Findings will be disseminated through peer-reviewed journals, reports to the funding body, conferences and other events for the scientific and clinical community, and the general public.Trial registration number NCT05094557.